In-situ RbSr dating of the crystalline basement beneath the Amadeus Basin, Australia: Implications for the radiogenic helium generation, migration and extreme 4He accumulation - Cecilia Loyola; Juraj Farkaš; Alan S. Collins; Jason Alexander Charlwood; Sarah E. Gilbert; Peter W. Haines (Chemical Geology, 2026)

Vancomycin-resistant Enterococcus faecium: a national wide genomic snapshot in Switzerland - Dominique S. Blanc; Florian Mauffrey; Andrea C. Büchler; Danielle Vuichard-Gysin; Vanja Piezzi; Céline Gardiol; Marc Garcia; Trestan Pillonel; Laurent Poirel; Patrice Nordmann; Pascal Schlaepfer; Claudio Neidhöfer; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Introduced or established? Convergent evidence indicates imported pine wood nematode vectors occupy gaps in native distribution - Jean-Claude Grégoire; Jean Artois; Julien Claude; Marius Gilbert; Serge Morand; Géraldine Roux; Gilles San Martin; Dimitrios Avtzis; Nick Berkvens; Jochem Bonte; Hans Casteels; Sandra Closa; et al. (Journal of Pest Science, 2026)
Monitoring regulated quarantine plant pathogens and, when relevant, their vectors is compulsory in the European Union. Local Monochamus species (Coleoptera, Cerambycidae) vector the pine wood nematode, Bursaphelenchus xylophilus , a non-native pest already established in most of Portugal. Only 29 M. galloprovincialis individuals were trapped in Belgium in ten years (2013–2022), despite a dense coverage of pheromone-baited traps, suggesting absence or a very rare local occurrence in the country. In the northern neighbouring countries, only one single established population is known in The Netherlands and one in Denmark. A species distribution model based on pheromone-trap catches (negative and positive) of M. galloprovincialis from 4,914 traps in 29 European countries between 2008 and 2019 was developed, using the overall climate conditions and the distribution of seven pine tree species as explanatory variables. The effect of spatial scale was tested with a multi-scale approach. With a 225*225 km spatial grain, the major explanatory variables were the mean diurnal temperature range and, to a lesser extent, the presence of Pinus spp. The model predicted a low probability of presence in Belgium, the Netherlands, Great Britain and north-western Germany compared to southern Europe. Genotyping allowed to conclude that at least some of the beetles caught in Belgium originated from foreign locations. All catches were located close to entry points, suggesting introduction with imported material. The small size of most of the Belgian pine stands may also explain the absence or apparently transient status, or rareness of Monochamus spp. This study thus suggests that surveys in Belgium should privilege entry points rather than local forest stands.

PTUPB improves cognitive function in Alzheimer’s disease associated with enhancing cerebral vascular myogenic response and attenuating vascular remodeling - Gilbert C. Morgan; Andrew Gregory; Chengyun Tang; Sung Hee Hwang; Jane J. Border; Jing Xu; Yedan Liu; Shan Bai; Tae Jin Lee; Cameron Cantwell; David Bunn; Karen M. Wagner; et al. (GeroScience, 2026)

Heterogeneity, Productivity, and Migration Drive Continental Evenness Patterns of Bird Assemblages - Neil A. Gilbert; Natalie Queally; Jacob C. Cooper; Harold N. Eyster; Peter J. Williams (Global Ecology and Biogeography, 2026)
Aim Evenness quantifies similarities in abundances among species in an assemblage and may influence processes such as species coexistence and the supply of ecosystem services. Previous work has failed to identify generalised patterns of how productivity and habitat heterogeneity influence evenness and moreover has not considered seasonal variation in evenness arising from migration. Therefore, our goal was to quantify the interplay of productivity, habitat heterogeneity, and migration on evenness patterns of bird assemblages. Location Contiguous United States. Time Period Contemporary. Group Birds (613 species). Methods Using relative abundance maps from eBird, we computed evenness of bird assemblages for 27 × 27 km grid cells at weekly temporal resolution. We used generalized linear mixed‐effects models to evaluate the influences of productivity (normalized difference vegetation index), habitat heterogeneity (Shannon diversity of land cover), and the dominance of migratory species on evenness. Results Productivity and heterogeneity interacted to influence evenness such that there was a positive productivity–evenness relationship in high‐heterogeneity landscapes but no relationship in low‐heterogeneity landscapes. Evenness was highest during the pre‐breeding and breeding seasons when migratory taxa were present, but a high dominance of migrants reduced evenness and generally dampened evenness–productivity relationships. Main Conclusions Evenness increased with productivity in high‐heterogeneity—but not low‐heterogeneity—landscapes, indicating that hypotheses relating to energy availability and niche partitioning should be considered jointly. Higher evenness during the growing season likely reflects the presence of low‐abundance migrant taxa, whereas the negative effects of migrant dominance on evenness are likely driven by one or few high‐abundance species. The dampening effect of migrant dominance on evenness–productivity relationships in many situations supports the notion that migrants concentrate in high‐productivity landscapes.

Continental Contrasts in Climate Extremes That Control Tree Fecundity - James S. Clark; Robert Andrus; Margarita Arianoutsou; Davide Ascoli; Yves Bergeron; Michal Bogdziewicz; Thomas Boivin; Raul Bonal; Thomas Caignard; Maxime Cailleret; Rafael Calama; J. Julio Camarero; et al. (Global Change Biology, 2026)
In 2023, more than half of olive harvests ( Olea europaea ) across Spain, Greece, and Türkiye were lost to drought. The same year late freeze destroyed 90% of the peach crop ( Prunus persica ) on the Georgia Piedmont and the apple crop ( Malus domestica ) in central New York, Vermont, and southern Quebec. Climate extremes now rank with the costliest threats to agriculture, but their role in forest recovery from diebacks that are happening globally is unknown for lack of tree fecundity estimates in forests. Tolerance of climate extremes could depend on past exposure but constrained by phylogenetic conservatism. We report a continental scale analysis of climate extremes and forest fecundity across North America and Europe showing that responses to late freeze and drought are happening now. Species differences are not explained by the traits typically included in ecological studies and they are weakly associated with phylogeny. Late freeze, that is, freezing temperatures that follow the onset of flower development in spring, is shown to be “normal” in North America, but not Europe, potentially explaining failed seed production due to delayed onset and the resultant shorter growing period by North American transplants dating back at least to the 18th century. Drought has thus far had the greatest impacts in dry forested regions, but here too, species differences are not explained by traditional trait values. If responses have been buffered from drought and late freeze by past exposure, acclimation and local adaptation prove inadequate as extremes intensify.

In situ Rb–Sr dating and REE analysis of glauconites and detrital feldspars from the Ediacaran/Cambrian strata: Centralian and Adelaide Superbasins, Australia - Cecilia Loyola; Juraj Farkaš; Alan S. Collins; Sarah E. Gilbert; Charles Verdel; Stefan C. Löhr; Glenn A. Brock; Graham A. Shields; Andre Baldermann; Ahmad Redaa; Morgan Blades; Darwinaji Subarkah; et al. (Precambrian Research, 2025)

Forest terpenes and stress: Examining the associations of filtered vs. non-filtered air in a real-life natural environment - Chaja M. Levy; Anne M. Riederer; Christopher D. Simpson; Amanda J. Gassett; Abigail J. Gilbert; Michael H. Paulsen; Lalith K. Silva; Deepak Bhandari; Cody A. Newman; Benjamin C. Blount; Peter H. Kahn; Gregory N. Bratman (Environmental Research, 2025)

Historical genomic variation of Eurasian otters (Lutra lutra) in Britain, from hunting trophies - Sarah J. du Plessis; Nuno F. Martins; Xin Sun; Sarah S. T. Mak; David W. G. Stanton; Klaus-Peter Koepfli; Elizabeth A. Chadwick; M. P. Thomas Gilbert; Frank Hailer (Conservation Genetics Resources, 2025)
Genomic data from historical specimens can provide insights into populations and processes no longer evident from modern samples. Identifying viable sources of historical DNA is key to this. Here we aimed to explore the viability of trophy hunting paws as sources of historical DNA, and to use this data for preliminary analyses to evaluate changes in population structuring over time. We aimed to search for the presence of genomic signals of the putative recent introduction of Eurasian otters ( Lutra lutra ) from Asia to the UK previously identified using modern data, by analysis of two trophy paws from 1929 to 1952. Substantial proportions of endogenous DNA (77–85%) were identified in both samples for which genomic DNA extraction and sequencing was attempted, illustrating the potential of such specimens for historical DNA research. Autosomal variation suggests that the historical specimens cluster closest to modern specimens from Wales, and not with the variation identified in the East of England, putatively associated with the recent introduction of Eurasian otters from Asia. Similarly, the divergent mitochondrial lineage found in modern otters from the East of England and Asia, was not found in the historical British specimens. Although limited inferences can be made from a sample size of two, this preliminary dataset indicates the huge potential of historical trophy paw samples to assess past population genetic dynamics, calling for further research in this area.

Adaptive sampling with PIXL on the Mars Perseverance rover - Peter R. Lawson; Tanya V. Kizovski; Michael M. Tice; Benton C. Clark; Scott J. VanBommel; David R. Thompson; Lawrence A. Wade; Robert W. Denise; Christopher M. Heirwegh; W. Timothy Elam; Mariek E. Schmidt; Yang Liu; et al. (Icarus, 2025)

Paleoenvironment, deposition conditions, and geochemical characteristics of the Permian Karoo hydrocarbon source rocks, Mid-Zambezi Basin, Zambia, based on paleontology and geochemistry studies: a review - Godfrey Peter Mweemba; Olubunmi C. Adeigbe; Gilbert M. Chongwain; Khady Ndeye Ndiaye (Arabian Journal of Geosciences, 2025)

Potential for large losses of carbon from non-native conifer plantations on deep peat over decadal timescales - Thomas J. Sloan; Joshua Ratcliffe; Russell Anderson; W. Roland Gehrels; Peter Gilbert; Dmitri Mauquoy; Anthony J. Newton; Richard J. Payne; Justyna Serafin; Roxane Andersen (Science of The Total Environment, 2024)

The role of annealing and grain boundary controls on the mechanical properties of limestones and marbles - Rui Zhang; Paul A. Bosomworth; Juliane Weber; Jan Ilavsky; Si Athena Chen; Alexis Flores-Betancourt; Elliot Paul Gilbert; Jitendra Mata; Mark L. Rivers; Peter J. Eng; Lawrence M. Anovitz (International Journal of Rock Mechanics and Mining Sciences, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

The Relationship Between Maturation Size and Maximum Tree Size From Tropical to Boreal Climates - Valentin Journé; Michał Bogdziewicz; Benoit Courbaud; Georges Kunstler; Tong Qiu; Marie‐Claire Aravena Acuña; Davide Ascoli; Yves Bergeron; Daniel Berveiller; Thomas Boivin; Raul Bonal; Thomas Caignard; et al. (Ecology Letters, 2024)
The fundamental trade‐off between current and future reproduction has long been considered to result in a tendency for species that can grow large to begin reproduction at a larger size. Due to the prolonged time required to reach maturity, estimates of tree maturation size remain very rare and we lack a global view on the generality and the shape of this trade‐off. Using seed production from five continents, we estimate tree maturation sizes for 486 tree species spanning tropical to boreal climates. Results show that a species' maturation size increases with maximum size, but in a non‐proportional way: the largest species begin reproduction at smaller sizes than would be expected if maturation were simply proportional to maximum size. Furthermore, the decrease in relative maturation size is steepest in cold climates. These findings on maturation size drivers are key to accurately represent forests' responses to disturbance and climate change.

Comparison of two carbonaceous supported Fe-rich adsorbents for arsenate removal: A functionalisation and mechanistic study with applicability to groundwater treatment - Sabolc Pap; Maja Turk Sekulic; Hai Nguyen Tran; Huan-Ping Chao; Peter J. Gilbert; Stuart W. Gibb; Mark A. Taggart (Chemosphere, 2024)

A global initiative for ecological and evolutionary hologenomics - Aoife Leonard; Javier Abalos; Titus Adhola; Windsor Aguirre; Ostaizka Aizpurua; Shahzad Ali; Franco Andreone; Fabien Aubret; Hefer D. Ávila-Palma; Lizbeth Fabiola Bautista Alcantara; Juan F. Beltrán; Rachel Berg; et al. (Trends in Ecology & Evolution, 2024)

A century of statistical Ecology - Neil A. Gilbert; Bruna R. Amaral; Olivia M. Smith; Peter J. Williams; Sydney Ceyzyk; Samuel Ayebare; Kayla L. Davis; Wendy Leuenberger; Jeffrey W. Doser; Elise F. Zipkin (Ecology, 2024)
As data and computing power have surged in recent decades, statistical modeling has become an important tool for understanding ecological patterns and processes. Statistical modeling in ecology faces two major challenges. First, ecological data may not conform to traditional methods, and second, professional ecologists often do not receive extensive statistical training. In response to these challenges, the journal Ecology has published many innovative statistical ecology papers that introduced novel modeling methods and provided accessible guides to statistical best practices. In this paper, we reflect on Ecology 's history and its role in the emergence of the subdiscipline of statistical ecology, which we define as the study of ecological systems using mathematical equations, probability, and empirical data. We showcase 36 influential statistical ecology papers that have been published in Ecology over the last century and, in so doing, comment on the evolution of the field. As data and computing power continue to increase, we anticipate continued growth in statistical ecology to tackle complex analyses and an expanding role for Ecology to publish innovative and influential papers, advancing the discipline and guiding practicing ecologists.

Uncovering neutral and adaptive genomic differentiation among European perch with brackish water and freshwater origin in the western Baltic Sea region - Mikkel Skovrind; George Pacheco; Emil Aputsiaq Flindt Christensen; Shyam Gopalakrishnan; Katharina Fietz; Tore Hejl Holm-Hansen; Filipe Garrett Vieira; Marcus Anders Krag; Henrik Carl; M.Thomas P. Gilbert; Morten Tange Olsen; Peter Rask Møller (Fisheries Research, 2023)

Why humans kill animals and why we cannot avoid it - Benjamin L. Allen; Christopher Bobier; Stuart Dawson; Peter J.S. Fleming; Jordan Hampton; David Jachowski; Graham I.H. Kerley; John D.C. Linnell; Kelly Marnewick; Liaan Minnie; Mike Muthersbaugh; M. Justin O'Riain; et al. (Science of The Total Environment, 2023)

Technical performance and economic efficiency of small-scale maize dryers in Kenya - Hugo De Groote; Peter Obuon Akoko; Richard Stroshine; Edith Gathungu; Jacob Ricker-Gilbert (Journal of Stored Products Research, 2023)

Organic carbon in British lowland ponds: estimating sediment stocks, possible practical benefits and significant unknowns - Michael J. Jeffries; Peter J. Gilbert; Scott Taylor; David A. Cooke; Michael E. Deary (Hydrobiologia, 2023)
Ponds are aquatic habitats defined by their small size. Although small they are found on every continent, they are disproportionately rich in aquatic biodiversity, benefit terrestrial wildlife and have important ecosystem function benefits. One of these benefits might be carbon sequestration, a possibility suggested by (1) their abundance, (2) the intensity of their biogeochemical activity. Whilst greenhouse gas fluxes from ponds have been monitored widely, quantifying the stocks of organic carbon buried in sediment is a gap in our knowledge. Here we summarise measures of organic carbon in pond sediments cores from a diverse range of lowland ponds in England. We estimate a general measure of 9.38 kg OC in a 1 m 2 × 20 cm block of pond sediment and scale this up to an overall estimate for Great Britain of 2.63 million tons of OC in pond sediment, with 95% CI of 1.41 to 3.84 million tons. The relationship between sediment carbon and gas fluxes remains a significant unknown.

Linking seed size and number to trait syndromes in trees - Michal Bogdziewicz; Marie‐Claire Aravena Acuña; Robert Andrus; Davide Ascoli; Yves Bergeron; Daniel Brveiller; Thomas Boivin; Raul Bonal; Thomas Caignard; Maxime Cailleret; Rafael Calama; Sergio Donoso Calderon; et al. (Global Ecology and Biogeography, 2023)
Aim Our understanding of the mechanisms that maintain forest diversity under changing climate can benefit from knowledge about traits that are closely linked to fitness. We tested whether the link between traits and seed number and seed size is consistent with two hypotheses, termed the leaf economics spectrum and the plant size syndrome, or whether reproduction represents an independent dimension related to a seed size–seed number trade‐off. Location Most of the data come from Europe, North and Central America and East Asia. A minority of the data come from South America, Africa and Australia. Time period 1960–2022. Major taxa studied Trees. Methods We gathered 12 million observations of the number of seeds produced in 784 tree species. We estimated the number of seeds produced by individual trees and scaled it up to the species level. Next, we used principal components analysis and generalized joint attribute modelling (GJAM) to map seed number and size on the tree traits spectrum. Results Incorporating seed size and number into trait analysis while controlling for environment and phylogeny with GJAM exposes relationships in trees that might otherwise remain hidden. Production of the large total biomass of seeds [product of seed number and seed size; hereafter, species seed productivity (SSP)] is associated with high leaf area, low foliar nitrogen, low specific leaf area (SLA) and dense wood. Production of high seed numbers is associated with small seeds produced by nutrient‐demanding species with softwood, small leaves and high SLA. Trait covariation is consistent with opposing strategies: one fast‐growing, early successional, with high dispersal, and the other slow‐growing, stress‐tolerant, that recruit in shaded conditions. Main conclusions Earth system models currently assume that reproductive allocation is indifferent among plant functional types. Easily measurable seed size is a strong predictor of the seed number and species seed productivity. The connection of SSP with the functional traits can form the first basis of improved fecundity prediction across global forests.

Assessing homogeneity of land surface air temperature observations using sparse‐input reanalyses - Ian Gillespie; Leo Haimberger; Gilbert P. Compo; Peter W. Thorne (International Journal of Climatology, 2023)
State‐of‐the‐art homogenisation approaches for any test site rely upon the availability of a sufficient number of neighbouring sites with similar climatic conditions and a sufficient quantity of overlapping measurements. These conditions are not always met, particularly in poorly sampled regions and epochs. Modern sparse‐input reanalysis products which are constrained by observed sea surface temperatures, sea‐ice and surface pressure observations, continue to improve, offering independently produced surface temperature estimates back to the early 19th century. This study undertakes an exploratory analysis on the applicability of sparse‐input reanalysis to identify breakpoints in available basic station data. Adjustments are then applied using a variety of reanalysis and neighbour‐based approaches to produce four distinct estimates. The methodological independence of the approach may offer valuable insights into historical data quality issues. The resulting estimates are compared to Global Historical Climatology Network version 4 (GHCNMv4) at various aggregations. Comparisons are also made with five existing global land surface monthly time series. We find a lower rate of long‐term warming which principally arises in differences in estimated behaviour prior to the early 20th century. Differences depend upon the exact pair of estimates, varying between 15 and 40% for changes from 1850–1900 to 2005–2014. Differences are much smaller for metrics starting after 1900 and negligible after 1950. Initial efforts at quantifying parametric uncertainty suggest this would be substantial and may lead to overlap between these new estimates and existing estimates. Further work would be required to use these data products in an operational context. This would include better understanding the reasons for apparent early period divergence including the impact of spatial infilling choices, quantification of parametric uncertainty, and a means to update the product post‐2015 when the NOAA‐CIRES‐DOE 20CRv3 sparse input reanalysis product, upon which they are based, presently ceases.

Aerobic respiration controls on shale weathering - Lucien Stolze; Bhavna Arora; Dipankar Dwivedi; Carl Steefel; Zhi Li; Sergio Carrero; Benjamin Gilbert; Peter Nico; Markus Bill (Geochimica et Cosmochimica Acta, 2023)

Globally, tree fecundity exceeds productivity gradients - Valentin Journé; Robert Andrus; Marie‐Claire Aravena; Davide Ascoli; Roberta Berretti; Daniel Berveiller; Michal Bogdziewicz; Thomas Boivin; Raul Bonal; Thomas Caignard; Rafael Calama; Jesús Julio Camarero; et al. (Ecology Letters, 2022)
Lack of tree fecundity data across climatic gradients precludes the analysis of how seed supply contributes to global variation in forest regeneration and biotic interactions responsible for biodiversity. A global synthesis of raw seedproduction data shows a 250‐fold increase in seed abundance from cold‐dry to warm‐wet climates, driven primarily by a 100‐fold increase in seed production for a given tree size. The modest (threefold) increase in forest productivity across the same climate gradient cannot explain the magnitudes of these trends. The increase in seeds per tree can arise from adaptive evolution driven by intense species interactions or from the direct effects of a warm, moist climate on tree fecundity. Either way, the massive differences in seed supply ramify through food webs potentially explaining a disproportionate role for species interactions in the wet tropics.

Ecological consequences of large herbivore exclusion in an A frican savanna: 12 years of data from the UHURU experiment - Jesse M. Alston; Courtney G. Reed; Leo M. Khasoha; Bianca R. P. Brown; Gilbert Busienei; Nathaniel Carlson; Tyler C. Coverdale; Megan Dudenhoeffer; Marissa A. Dyck; John Ekeno; Abdikadir A. Hassan; Rhianna Hohbein; et al. (Ecology, 2022)
Diverse communities of large mammalian herbivores (LMH), once widespread, are now rare. LMH exert strong direct and indirect effects on community structure and ecosystem functions, and measuring these effects is important for testing ecological theory and for understanding past, current, and future environmental change. This in turn requires long‐term experimental manipulations, owing to the slow and often nonlinear responses of populations and assemblages to LMH removal. Moreover, the effects of particular species or body‐size classes within diverse LMH guilds are difficult to pinpoint, and the magnitude and even direction of these effects often depends on environmental context. Since 2008, we have maintained the Ungulate Herbivory Under Rainfall Uncertainty (UHURU) experiment, a series of size‐selective LMH exclosures replicated across a rainfall/productivity gradient in a semiarid Kenyan savanna. The goals of the UHURU experiment are to measure the effects of removing successively smaller size classes of LMH (mimicking the process of size‐biased extirpation) and to establish how these effects are shaped by spatial and temporal variation in rainfall. The UHURU experiment comprises three LMH‐exclusion treatments and an unfenced control, applied to nine randomized blocks of contiguous 1‐ha plots ( n = 36). The fenced treatments are MEGA (exclusion of megaherbivores, elephant and giraffe), MESO (exclusion of herbivores ≥40 kg), and TOTAL (exclusion of herbivores ≥5 kg). Each block is replicated three times at three sites across the 20‐km rainfall gradient, which has fluctuated over the course of the experiment. The first 5 years of data were published previously ( Ecological Archives E095‐064) and have been used in numerous studies. Since that publication, we have (1) continued to collect data following the original protocols, (2) improved the taxonomic resolution and accuracy of plant and small‐mammal identifications, and (3) begun collecting several new data sets. Here, we present updated and extended raw data from the first 12 years of the UHURU experiment (2008–2019). Data include daily rainfall data throughout the experiment; annual surveys of understory plant communities; annual censuses of woody‐plant communities; annual measurements of individually tagged woody plants; monthly monitoring of flowering and fruiting phenology; every‐other‐month small‐mammal mark–recapture data; and quarterly large‐mammal dung surveys. There are no copyright restrictions; notification of when and how data are used is appreciated and users of UHURU data should cite this data paper when using the data.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

The virtual goniometer: demonstrating a new method for measuring angles on archaeological materials using fragmentary bone - Katrina Yezzi-Woodley; Jeff Calder; Peter J. Olver; Paige Cody; Thomas Huffstutler; Alexander Terwilliger; J. Anne Melton; Martha Tappen; Reed Coil; Gilbert Tostevin (Archaeological and Anthropological Sciences, 2021)

Abundance and biogeography of methanogenic and methanotrophic microorganisms across European streams - Magdalena Nagler; Nadine Praeg; Georg H. Niedrist; Katrin Attermeyer; Núria Catalán; Francesca Pilotto; Catherine Gutmann Roberts; Christoph Bors; Stefano Fenoglio; Miriam Colls; Sophie Cauvy‐Fraunié; Brian Doyle; et al. (Journal of Biogeography, 2021)
Aim Although running waters are getting recognized as important methane sources, large‐scale geographical patterns of microorganisms controlling the net methane balance of streams are still unknown. Here we aim at describing community compositions of methanogenic and methanotrophic microorganisms at large spatial scales and at linking their abundances to potential sediment methane production (PMP) and oxidation rates (PMO). Location The study spans across 16 European streams from northern Spain to northern Sweden and from western Ireland to western Bulgaria. Taxon Methanogenic archaea and methane‐oxidizing microorganisms. Methods To provide a geographical overview of both groups in a single approach, microbial communities and abundances were investigated via 16S rRNA gene sequencing, extracting relevant OTUs based on literature; both groups were quantified via quantitative PCR targeting mcrA and pmoA genes and studied in relation to environmental parameters, sediment PMP and PMO, and land use. Results Diversity of methanogenic archaea was higher in warmer streams and of methanotrophic communities in southern sampling sites and in larger streams. Anthropogenically altered, warm and oxygen‐poor streams were dominated by the highly efficient methanogenic families Methanospirillaceae , Methanosarcinaceae and Methanobacteriaceae , but did not harbour any specific methanotrophic organisms. Contrastingly, sediment communities in colder, oxygen‐rich waters with little anthropogenic impact were characterized by methanogenic Methanosaetaceae , Methanocellaceae and Methanoflorentaceae and methanotrophic Methylococcaceae and Cd . Methanoperedens. Representatives of the methanotrophic Crenotrichaceae and Methylococcaceae as well as the methanogenic Methanoregulaceae were characteristic for environments with larger catchment area and higher discharge. PMP increased with increasing abundance of methanogenic archaea, while PMO rates did not show correlations with abundances of methane‐oxidizing bacteria. Main conclusions Methanogenic and methanotrophic communities grouping into three habitat types suggest that future climate‐ and land use changes may influence the prevailing microbes involved in the large‐scale stream‐related methane cycle, favouring the growth of highly efficient hydrogenotrophic methane producers. Based on these results, we expect global change effect on PMP rates to especially impact rivers adjacent to anthropogenically disturbed land uses.

Assessing potential of sparse‐input reanalyses for centennial‐scale land surface air temperature homogenisation - Ian M. Gillespie; Leo Haimberger; Gilbert P. Compo; Peter W. Thorne (International Journal of Climatology, 2021)
Observations from the historical meteorological observing network contain many artefacts of non‐climatic origin which must be accounted for prior to using these data in climate applications. State‐of‐the‐art homogenisation approaches use various flavours of pairwise comparison between a target station and candidate neighbour station series. Such approaches require an adequate number of neighbours of sufficient quality and comparability – a condition that is met for most station series since the mid‐20th Century. However, pairwise approaches have challenges where suitable neighbouring stations are sparse, as remains the case in vast regions of the globe and is common almost everywhere prior to the early 20th Century. Modern sparse‐input centennial reanalysis products continue to improve and offer a potential alternative to pairwise comparison, particularly where and when observations are sparse. They do not directly ingest or use land‐based surface temperature observations, so they are a formally independent estimate. This may be particularly helpful in cases where structurally similar changes exist across broad networks, which challenges current techniques in the absence of metadata. They also potentially offer a valuable methodologically distinct method, which would help explore structural uncertainty in homogenisation techniques. The present study compares the potential of spatially‐interpolated sparse‐input reanalysis products to neighbour‐based approaches to perform homogenisation of global monthly land surface air temperature records back to 1850 based upon the statistical properties of station‐minus‐reanalysis and station‐minus‐neighbour series. This shows that neighbour‐based approaches likely remain preferable in data dense regions and epochs. However, the most recent reanalysis product, NOAA‐CIRES‐DOE 20CRv3, is potentially preferable in cases where insufficient neighbours are available. This may in particular affect long‐term global average estimates where a small number of long‐term stations in data sparse regions will make substantial contributions to global estimates and may contain missed data artefacts in present homogenisation approaches.

Argo Data 1999–2019: Two Million Temperature-Salinity Profiles and Subsurface Velocity Observations From a Global Array of Profiling Floats - Annie P. S. Wong; Susan E. Wijffels; Stephen C. Riser; Sylvie Pouliquen; Shigeki Hosoda; Dean Roemmich; John Gilson; Gregory C. Johnson; Kim Martini; David J. Murphy; Megan Scanderbeg; T. V. S. Udaya Bhaskar; et al. (Frontiers in Marine Science, 2020)

Climate and local environment structure asynchrony and the stability of primary production in grasslands - Benjamin Gilbert; Andrew S. MacDougall; Taku Kadoya; Munemitsu Akasaka; Joseph R. Bennett; Eric M. Lind; Habacuc Flores‐Moreno; Jennifer Firn; Yann Hautier; Elizabeth T. Borer; Eric W. Seabloom; Peter B. Adler; et al. (Global Ecology and Biogeography, 2020)
Aim Climate variability threatens to destabilize production in many ecosystems. Asynchronous species dynamics may buffer against such variability when a decrease in performance by some species is offset by an increase in performance of others. However, high climatic variability can eliminate species through stochastic extinctions or cause similar stress responses among species that reduce buffering. Local conditions, such as soil nutrients, can also alter production stability directly or by influencing asynchrony. We test these hypotheses using a globally distributed sampling experiment. Location Grasslands in North America, Europe and Australia. Time period Annual surveys over 5 year intervals occurring between 2007 and 2014. Major taxa studied Herbaceous plants. Methods We sampled annually the per species cover and aboveground community biomass [net primary productivity (NPP)], plus soil chemical properties, in 29 grasslands. We tested how soil conditions, combined with variability in precipitation and temperature, affect species richness, asynchrony and temporal stability of primary productivity. We used bivariate relationships and structural equation modelling to examine proximate and ultimate relationships. Results Climate variability strongly predicted asynchrony, whereas NPP stability was more related to soil conditions. Species richness was structured by both climate variability and soils and, in turn, increased asynchrony. Variability in temperature and precipitation caused a unimodal asynchrony response, with asynchrony being lowest at low and high climate variability. Climate impacted stability indirectly, through its effect on asynchrony, with stability increasing at higher asynchrony owing to lower inter‐annual variability in NPP. Soil conditions had no detectable effect on asynchrony but increased stability by increasing the mean NPP, especially when soil organic matter was high. Main conclusions We found globally consistent evidence that climate modulates species asynchrony but that the direct effect on stability is low relative to local soil conditions. Nonetheless, our observed unimodal responses to variability in temperature and precipitation suggest asynchrony thresholds, beyond which there are detectable destabilizing impacts of climate on primary productivity.

Ancient DNA suggests modern wolves trace their origin to a Late Pleistocene expansion from Beringia - Liisa Loog; Olaf Thalmann; Mikkel‐Holger S. Sinding; Verena J. Schuenemann; Angela Perri; Mietje Germonpré; Herve Bocherens; Kelsey E. Witt; Jose A. Samaniego Castruita; Marcela S. Velasco; Inge K. C. Lundstrøm; Nathan Wales; et al. (Molecular Ecology, 2020)
Grey wolves ( Canis lupus ) are one of the few large terrestrial carnivores that have maintained a wide geographical distribution across the Northern Hemisphere throughout the Pleistocene and Holocene. Recent genetic studies have suggested that, despite this continuous presence, major demographic changes occurred in wolf populations between the Late Pleistocene and early Holocene, and that extant wolves trace their ancestry to a single Late Pleistocene population. Both the geographical origin of this ancestral population and how it became widespread remain unknown. Here, we used a spatially and temporally explicit modelling framework to analyse a data set of 90 modern and 45 ancient mitochondrial wolf genomes from across the Northern Hemisphere, spanning the last 50,000 years. Our results suggest that contemporary wolf populations trace their ancestry to an expansion from Beringia at the end of the Last Glacial Maximum, and that this process was most likely driven by Late Pleistocene ecological fluctuations that occurred across the Northern Hemisphere. This study provides direct ancient genetic evidence that long‐range migration has played an important role in the population history of a large carnivore, and provides insight into how wolves survived the wave of megafaunal extinctions at the end of the last glaciation. Moreover, because Late Pleistocene grey wolves were the likely source from which all modern dogs trace their origins, the demographic history described in this study has fundamental implications for understanding the geographical origin of the dog.

Age progression from vicenarians (20–29 year) to nonagenarians (90–99 year) among a population pharmacokinetic/pharmacodynamic (PopPk-PD) covariate analysis of propofol-bispectral index (BIS) electroencephalography - Ashraf A. Dahaba; Zhaoyang Xiao; Xiaoling Zhu; Hailong Dong; Lize Xiong; Peter Rehak; Sieglinde Zelzer; Kun Wang; Gilbert Reibnegger (Journal of Pharmacokinetics and Pharmacodynamics, 2020)

Effects of the Bioturbating Marine Yabby Trypaea australiensis on Sediment Properties in Sandy Sediments Receiving Mangrove Leaf Litter - Ryan J. K. Dunn; David T. Welsh; Peter R. Teasdale; Franck Gilbert; Jean-Christophe Poggiale; Nathan J. Waltham (Journal of Marine Science and Engineering, 2019)
Laboratory mesocosm incubations were undertaken to investigate the influence of burrowing shrimp Trypaea australiensis (marine yabby) on sediment reworking, physical and chemical sediment characteristics and nutrients in sandy sediments receiving mangrove (Avicennia marina) leaf litter. Mesocosms of sieved, natural T. australiensis inhabited sands, were continually flushed with fresh seawater and pre-incubated for 17 days prior to triplicates being assigned to one of four treatments; sandy sediment (S), sediment + yabbies (S+Y), sediment + leaf litter (organic matter; S+OM) and sediment + yabbies + leaf litter (S+Y+OM) and maintained for 55 days. Mangrove leaf litter was added daily to treatments S+OM and S+Y+OM. Luminophores were added to mesocosms to quantify sediment reworking. Sediment samples were collected after the pre-incubation period from a set of triplicate mesocosms to establish initial conditions prior to the imposition of the treatments and from the treatment mesocosms at the conclusion of the 55-day incubation period. Yabbies demonstrated a clear effect on sediment topography and leaf litter burial through burrow creation and maintenance, creating mounds on the sediment surface ranging in diameter from 3.4 to 12 cm. Within S+Y+OM sediments leaf litter was consistently removed from the surface to sub-surface layers with only 7.5% ± 3.6% of the total mass of leaf detritus added to the mesocosms remaining at the surface at the end of the 55-day incubation period. Yabbies significantly decreased sediment wet-bulk density and increased porosity. Additionally, T. australiensis significantly reduced sediment bio-available ammonium (NH4+bio) concentrations and altered the shape of the concentration depth profile in comparison to the non-bioturbated mesocosms, indicating influences on nutrient cycling and sediment-water fluxes. No significant changes for mean apparent biodiffusion coefficients (Db) and mean biotransport coefficients (r), were found between the bioturbated S+Y and S+Y+OM mesocosms. The findings of this study provide further evidence that T. australiensis is a key-species in shallow intertidal systems playing an important role as an ‘ecosystem engineer’ in soft-bottom habitats by significantly altering physical and chemical structures and biogeochemical function.

Stand inventory data from the 10‐ha forest research plot in Uholka: 15 yr of primeval beech forest development - Jonas Stillhard; Martina Hobi; Lisa Hülsmann; Peter Brang; Christian Ginzler; Myroslav Kabal; Jens Nitzsche; Gilbert Projer; Yuriy Shparyk; Brigitte Commarmot (Ecology, 2019)
Forests dominated by European beech ( Fagus sylvatica L.) are among both the most widespread in Europe and the most intensely exploited globally. One of the largest remnants of unmanaged beech forests in Europe is the Uholka‐Shyrokyi Luh forest in Transcarpathia, Ukraine, covering 8,800 ha of primeval forest. In 2000, a permanent forest plot of 10 ha has been established in the Uholka massif. All living and dead trees with a diameter at breast height ( DBH ) ≥ 60 mm were identified to species, DBH measured, stems tagged and mapped. Since then, the plot has been remeasured in 2005, 2010, and 2015. In total, 4,820 individual trees were measured with 14,116 individual measurements throughout all four inventories. In spring 2018, an Airborne Laser Scan was carried out, covering the Uholka‐Shyrokyi Luh forest. This data set allows us to derive a high‐resolution digital elevation model ( DEM ) of the plot area. European beech covers a share of ≈ 95% of the basal area ( BA ) of all living stems. While BA was relatively stable throughout all inventories (≈ 38 m 2 /ha), the number of stems increased considerably between 2010 and 2015 from 290 to 430 stems/ha. Additionally, the proportion of beech stems decreased from 95% in 2010 to 86% in 2015. The continuity of the share of beech on BA and the decrease in number of stems can be traced back to disturbance events, which led to an increase of more light demanding species in the recruitment but did not alter the distribution of BA as these small trees contribute very little to BA . The data set allows for important insights into the development and the spatial and temporal dynamics of primeval beech forests. It can be used to quantify the demographic processes growth, mortality, and recruitment, and to study inter‐ and intraspecific effects on demographic rates, stand structure, and species composition. No copyright or proprietary restrictions are associated with the use of this data set other than citation of this Data Paper.

Labelling halophilic Archaea using 13C and 15N stable isotopes: a potential tool to investigate haloarchaea consumption by metazoans - R. M. A. Lopes-dos-Santos; Marleen De Troch; Peter Bossier; Gilbert Van Stappen (Extremophiles, 2019)

Predation drives recurrent convergence of an interspecies mutualism - William E. Feeney; Rohan M. Brooker; Lane N. Johnston; James D. J. Gilbert; Marc Besson; David Lecchini; Danielle L. Dixson; Peter F. Cowman; Andrea Manica (Ecology Letters, 2019)
Mutualisms are important ecological interactions that underpin much of the world's biodiversity. Predation risk has been shown to regulate mutualism dynamics in species‐specific case studies; however, we lack studies which investigate whether predation can also explain broader patterns of mutualism evolution. We report that fish‐anemone mutualisms have evolved on at least 55 occasions across 16 fish families over the past 60 million years and that adult body size is associated with the ontogenetic stage of anemone mutualisms: larger‐bodied species partner with anemones as juveniles, while smaller‐bodied species partner with anemones throughout their lives. Field and laboratory studies show that predators target smaller prey, that smaller fishes associate more with anemones, and that these relationships confer protection to small fishes. Our results indicate that predation is likely driving the recurrent convergent evolution of fish‐anemone mutualisms and suggest that similar ecological processes may have selected convergence in interspecies interactions in other animal clades.

Bacteria as food in aquaculture: do they make a difference? - Nancy Nevejan; Peter De Schryver; Mathieu Wille; Kristof Dierckens; Kartik Baruah; Gilbert Van Stappen (Reviews in Aquaculture, 2018)
Bacterioplankton is an important component of marine as well as fresh waters and accounts for a large fraction of the production of particulate matter in those ecosystems. The concept of bacteria as providers of essential nutrients in aquatic food webs has been raised most recently in relation to the utilization of bacteria as a food source in aquaculture food chains. This article represents a comprehensive review on the potential role of bacteria as a direct food source for aquaculture organisms. After studying shortly the analytical tools that can be applied to determine the uptake and assimilation of bacteria by higher trophic levels, it describes the bacterial loads that are found in closed and open aquaculture systems and elaborates on the composition of bacteria from a nutritional point of view. Next this study elaborates in more detail on the role of bacteria as food for the zooplankton groups used as live food in aquaculture hatcheries and for various groups of aquaculture target organisms, such as fish, crustaceans and especially bivalves. This includes an assessment of the specific uptake mechanisms of the different taxonomic groups of interest in relation to their efficiency to ingest bacteria. Finally, future research lines are suggested to elucidate the nutritional impact of the bacterial community in aquaculture systems and how to steer this in order to optimize the production.

Quantifying rapid spatial and temporal variations of CO2 fluxes from small, lowland freshwater ponds - Peter J. Gilbert; David A. Cooke; Michael Deary; Scott Taylor; Michael J. Jeffries (Hydrobiologia, 2017)

Leaf anatomy of two reciprocally non-monophyletic mountain plants (Heliosperma spp.): does heritable adaptation to divergent growing sites accompany the onset of speciation? - Clara Bertel; Peter Schönswetter; Božo Frajman; Andreas Holzinger; Gilbert Neuner (Protoplasma, 2017)

Hydration/dehydration cycles imposed on Artemia cysts influence the tolerance limit of nauplii against abiotic and biotic stressors - Mohamed Omar El-Magsodi; Kartik Baruah; Parisa Norouzitallab; Peter Bossier; Patrick Sorgeloos; Gilbert Van Stappen (Aquaculture International, 2016)

Widespread Chemical Detoxification of Alkaloid Venom by Formicine Ants - Edward G. LeBrun; Peter J. Diebold; Matthew R. Orr; Lawrence E. Gilbert (Journal of Chemical Ecology, 2015)

Arsenic hazard in Cambodian rice from a market-based survey with a case study of Preak Russey village, Kandal Province - Peter J. Gilbert; David A. Polya; David A. Cooke (Environmental Geochemistry and Health, 2015)

Hatching and nutritional quality of Artemia cysts progressively deteriorates as a function of increased exposure to hydration/dehydration cycles - Mohamed Omar El-Magsodi; Peter Bossier; Patrick Sorgeloos; Gilbert Van Stappen (Aquaculture International, 2014)

Understanding the Needs of Colorectal Cancer Patients during the Pre-diagnosis Phase - David Wiljer; Tara Walton; Julie Gilbert; Amy Boucher; Peter M Ellis; Susan Schiff; Scott M Sellick; Marko Simunovic; Erin Kennedy; Sara Urowitz (Journal of Cancer Education, 2013)

Biomass Production and Composition of Perennial Grasses Grown for Bioenergy in a Subtropical Climate Across Florida, USA - Jeffrey R. Fedenko; John E. Erickson; Kenneth R. Woodard; Lynn E. Sollenberger; Joao M. B. Vendramini; Robert. A. Gilbert; Zane R. Helsel; Gary F. Peter (BioEnergy Research, 2013)

Two‐Stage Recovery of Amphibian Assemblages Following Selective Logging of Tropical Forests - GILBERT BAASE ADUM; MARKUS PETER EICHHORN; WILLIAM ODURO; CALEB OFORI‐BOATENG; MARK‐OLIVER RÖDEL (Conservation Biology, 2013)
There is a lack of quantitative information on the effectiveness of selective‐logging practices in ameliorating effects of logging on faunal communities. We conducted a large‐scale replicated field study in 3 selectively logged moist semideciduous forests in West Africa at varying times after timber extraction to assess post logging effects on amphibian assemblages. Specifically, we assessed whether the diversity, abundance, and assemblage composition of amphibians changed over time for forest‐dependent species and those tolerant of forest disturbance. In 2009, we sampled amphibians in 3 forests (total of 48 study plots, each 2 ha) in southwestern Ghana. In each forest, we established plots in undisturbed forest, recently logged forest, and forest logged 10 and 20 years previously. Logging intensity was constant across sites with 3 trees/ha removed. Recently logged forests supported substantially more species than unlogged forests. This was due to an influx of disturbance‐tolerant species after logging. Simultaneously Simpson's index decreased, with increased in dominance of a few species. As time since logging increased richness of disturbance‐tolerant species decreased until 10 years after logging when their composition was indistinguishable from unlogged forests. Simpson's index increased with time since logging and was indistinguishable from unlogged forest 20 years after logging. Forest specialists decreased after logging and recovered slowly. However, after 20 years amphibian assemblages had returned to a state indistinguishable from that of undisturbed forest in both abundance and composition. These results demonstrate that even with low‐intensity logging (≤3 trees/ha) a minimum 20‐year rotation of logging is required for effective conservation of amphibian assemblages in moist semideciduous forests. Furthermore, remnant patches of intact forests retained in the landscape and the presence of permanent brooks may aid in the effective recovery of amphibian assemblages. Recuperación de Ensambles de Anfibios en Dos Etapas Después de la Tala Selectiva de Bosques Tropicales

Bayesian inference of a complex invasion history revealed by nuclear and chloroplast genetic diversity in the colonizing plant, S ilene latifolia - Stephen R. Keller; Kimberly J. Gilbert; Peter D. Fields; Douglas R. Taylor (Molecular Ecology, 2012)
Species invading new ranges are subject to a series of demographic events that can strongly shape genetic diversity. Describing this demographic history is important for understanding where invasive species come from and how they spread, and is critical to testing hypotheses of postinvasion adaptation. Here, we analyse nuclear and chloroplast genetic diversity to study the invasion history of the widespread colonizing weed, S ilene latifolia ( C aryophyllaceae). Bayesian clustering and PCA revealed strong population structure in the native range of Europe, and although genotypes from multiple native sources were present in the introduced range of North America, the spatial distribution of genetic variance was dramatically reorganized. Using approximate B ayesian computation ( ABC ), we compared support for different invasion scenarios, including the number and size of independent introduction events and the amount of admixture occurring between sources of introduced genotypes. Our results supported independent introductions into eastern and western North America, with the latter forming a bridgehead for a secondary invasion into the G reat L akes region of central N orth A merica. Despite small estimated founder population sizes, the duration of the demographic bottleneck after the initial introduction appeared extremely short‐lived. This pattern of repeated colonization and rapid expansion has effectively eroded the strong population structure and cytonuclear associations present in Europe, but has retained overall high genetic diversity since invasion. Our results highlight the flexibility of the ABC approach for constructing a narrative of the demographic history of species invasions and provide baseline for future studies of evolutionary changes in introduced S. latifolia populations.

Microbial consortia increase thermal tolerance of corals - Justine A. Gilbert; Ross Hill; Martina A. Doblin; Peter J. Ralph (Marine Biology, 2012)

Understanding the needs of lung cancer patients during the pre-diagnosis phase - David Wiljer; Tara Walton; Julie Gilbert; Amy Boucher; Peter M Ellis; Susan Schiff; Scott M Sellick; Marko Simunovic; Andrea Bezjak; Sara Urowitz (Journal of Cancer Education, 2012)

Evaluation of a microbiological screening and acceptance procedure for cryopreserved skin allografts based on 14 day cultures - Jean-Paul Pirnay; Gunther Verween; Bruno Pascual; Gilbert Verbeken; Peter De Corte; Thomas Rose; Serge Jennes; Alain Vanderkelen; Miriam Marichal; Walter Heuninckx; Daniel De Vos (Cell and Tissue Banking, 2012)

A novel approach of homozygous haplotype sharing identifies candidate genes in autism spectrum disorder - Jillian P. Casey; Tiago Magalhaes; Judith M. Conroy; Regina Regan; Naisha Shah; Richard Anney; Denis C. Shields; Brett S. Abrahams; Joana Almeida; Elena Bacchelli; Anthony J. Bailey; Gillian Baird; et al. (Human Genetics, 2012)

Feeder layer- and animal product-free culture of neonatal foreskin keratinocytes: improved performance, usability, quality and safety - Peter De Corte; Gunther Verween; Gilbert Verbeken; Thomas Rose; Serge Jennes; Arlette De Coninck; Diane Roseeuw; Alain Vanderkelen; Eric Kets; David Haddow; Jean-Paul Pirnay (Cell and Tissue Banking, 2012)

Glycerol treatment as recovery procedure for cryopreserved human skin allografts positive for bacteria and fungi - Gilbert Verbeken; Gunther Verween; Daniel De Vos; Bruno Pascual; Peter De Corte; Cornelia Richters; Arlette De Coninck; Diane Roseeuw; Nadine Ectors; Thomas Rose; Serge Jennes; Jean-Paul Pirnay (Cell and Tissue Banking, 2012)

Potential release of aluminum and other metals by food-grade aluminum foil used for skin allograft cryo preservation - Gilbert Verbeken; Dirck Schoeters; Gunther Verween; Daniel De Vos; Bruno Pascual; Peter De Corte; Kris Geukens; Arlette De Coninck; Diane Roseeuw; Thomas Rose; Serge Jennes; Jean-Paul Pirnay (Cell and Tissue Banking, 2011)

Erratum to: Resolving Myoarchitectural Disarray in the Mouse Ventricular Wall with Diffusion Spectrum Magnetic Resonance Imaging - Teresa T. Wang; Hyuk Sang Kwon; Guangping Dai; Ruopeng Wang; Srboljub M. Mijailovich; Richard L. Moss; Peter T. C. So; Van J. Wedeen; Richard J. Gilbert (Annals of Biomedical Engineering, 2010)

Resolving Myoarchitectural Disarray in the Mouse Ventricular Wall with Diffusion Spectrum Magnetic Resonance Imaging - Teresa T. Wang; Hyuk Sang Kwon; Guangping Dai; Ruopeng Wang; Srboljub M. Mijailovich; Richard L. Moss; Peter T. C. So; Van J. Wedeen; Richard J. Gilbert (Annals of Biomedical Engineering, 2010)

Connectivity, non‐random extinction and ecosystem function in experimental metacommunities - Philip Staddon; Zoë Lindo; Peter D. Crittenden; Francis Gilbert; Andrew Gonzalez (Ecology Letters, 2010)
Ecology Letters (2010) 13: 543–552 Abstract The spatial insurance hypothesis indicates that connectivity is an important attribute of natural ecosystems that sustains both biodiversity and ecosystem function. We tested the hypothesis by measuring the impact of manipulating connectivity in experimental metacommunties of a natural and diverse microecosystem. Isolation led to the extinction of large‐bodied apex predators, subsequently followed by increases in prey species abundance. This trophic cascade was associated with significantly altered carbon and nitrogen fluxes in fragmented treatments. The ecosystem impacts were characteristic of a function debt because they persisted for several generations after the initial loss of connectivity. Local extinctions and disruption of ecosystem processes were mitigated, and even reversed, by the presence of corridors in the connected metacommunities, although these beneficial effects were unexpectedly delayed. We hypothesized that corridors maintained grazer movement between fragments, which enhanced microbial activity, and decomposition in comparison to isolated fragments. Our results indicate that knowledge of habitat connectivity and spatial processes is essential to understand the magnitude and timing of ecosystem perturbation in fragmented landscapes.

A multidisciplinary study of archaeological grape seeds - Enrico Cappellini; M. Thomas P. Gilbert; Filippo Geuna; Girolamo Fiorentino; Allan Hall; Jane Thomas-Oates; Peter D. Ashton; David A. Ashford; Paul Arthur; Paula F. Campos; Johan Kool; Eske Willerslev; et al. (The Science of Nature, 2010)

Effects of Male Age and Cervical Proprioceptors on Sexual Aerial Pursuit by Male Flesh Flies, Neobellieria bullata (Diptera: Sarcophagidae) - Cole Gilbert; Min Peter Kim (Journal of Insect Behavior, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Identification of host range mutants of myxoma virus with altered oncolytic potential in human glioma cells - John W Barrett; Lindsay R Alston; Fuan Wang; Marianne M Stanford; Philippe-Alexandre Gilbert; Xiujuan Gao; June Jimenez; Danielle Villeneuve; Peter Forsyth; Grant McFadden (Journal of NeuroVirology, 2007)

Next-day residual effects of hypnotics in DSM-IV primary insomnia: a driving simulator study with simultaneous electroencephalogram monitoring - Luc Staner; Stéphane Ertlé; Peter Boeijinga; Gilbert Rinaudo; Marie Agnès Arnal; Alain Muzet; Rémy Luthringer (Psychopharmacology, 2005)

Reliability of maximal muscle force and voluntary activation as markers of exercise-induced muscle damage - James Peter Morton; Greg Atkinson; Donald PM MacLaren; Nigel Tim Cable; Gareth Gilbert; Caroline Broome; Anne McArdle; Barry Drust (European Journal of Applied Physiology, 2005)

Differentially expressed genes associated with dormancy or germination of Arabidopsis thaliana seeds - Peter E. Toorop; Rosa Maria Barroco; Gilbert Engler; Steven P. C. Groot; Henk W. M. Hilhorst (Planta, 2005)

Management of Wetlands - AlisonJ. Gilbert; Hasse Goosen; Peter van der Werff (Regional Environmental Change, 2004)

Cellular apoptosis susceptibility gene Capts maps to mouse Chromosome 2 - Maria de Miguel; John M. Centanni; Ganesan Gopalan; Debra J. Gilbert; Neal G. Copeland; Nancy A. Jenkins; Peter J. Donovan (Mammalian Genome, 1998)

Interleukin-1 receptor-associated kinase gene Il1rak maps to the mouse X Chromosome - John M. Centanni; Maria de Miguel; Ganesan Gopalan; Debra J. Gilbert; Neal G. Copeland; Nancy A. Jenkins; Peter J. Donovan (Mammalian Genome, 1998)

Chromosome localization of two new mammalian kinases related to yeast and fly chromosome segregation-regulators - Ganesan Gopalan; Debra J. Gilbert; Neal G. Copeland; Nancy A. Jenkins; Peter J. Donovan (Mammalian Genome, 1998)

RNA virus-like particles in the chytridiomycete Allomyces arbuscula - Edward W. Khandjian; Urs-Peter Roos; William E. Timberlake; Lorenza Eder; Gilbert Turian (Archives of Microbiology, 1974)